Crane Site and the Palaeoeskimo Period in the Western Canadian Arctic - Le Blanc, Raymond Joseph (Book collections on Project MUSE., 1994)
The similarities shared by the Crane site, Cape Bathurst Peninsula, NWT with Lagoon Site on Banks Island, as well as comparable material on Melville Island, provide the basis for the definition of a regional cultural complex that existed during the period of change from the Pre-Dorset to the Dorset phases of the Palaeoeskimo continuum.